2015
DOI: 10.5688/ajpe79335
|View full text |Cite
|
Sign up to set email alerts
|

An International Comparison Study of Pharmacy Students’ Achievement Goals and their Relationship to Assessment Type and Scores

Abstract: Objective: To identify pharmacy students' preferred achievement goals in a multi-national undergraduate population, to investigate achievement goal preferences across comparable degree programs, and to identify relationships between achievement goals, academic performance, and assessment type. Methods: The Achievement Goal Questionnaire was administered to second year students in 4 universities in Australia, New Zealand, England, and Wales. Academic performance was measured using total scores, multiple-choice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In fact, it is well acknowledged that pharmacy students exhibit an overall preference for the mastery-approach goal orientation and demonstrate substantial intrinsic motivational characteristics. 35,36 Pharmacy students are meta-cognitively aware of their motivation to learn and selfregulate their learning, and, as such, they highly value their learning behaviors. performing students with an opportunity to excel and be rewarded accordingly, an opportunity that was clearly unexploited through the flipped exam.…”
Section: A J P E a C C E P T E D D R A F Tmentioning
confidence: 99%
“…In fact, it is well acknowledged that pharmacy students exhibit an overall preference for the mastery-approach goal orientation and demonstrate substantial intrinsic motivational characteristics. 35,36 Pharmacy students are meta-cognitively aware of their motivation to learn and selfregulate their learning, and, as such, they highly value their learning behaviors. performing students with an opportunity to excel and be rewarded accordingly, an opportunity that was clearly unexploited through the flipped exam.…”
Section: A J P E a C C E P T E D D R A F Tmentioning
confidence: 99%
“…The findings suggest that mastery-approach students would adopt self-reflection strategies at higher rates than performance-approach students. A similar pattern was found in a study of motivational orientations in pharmacy students and their exam scores on multiple-choice and short-essay exams [57]. Findings indicated that the masteryapproach orientation correlates with higher scores on essay exams, while performance-avoidance orientations correlate with lower scores on either exam type.…”
Section: Major Findings From the Theories -Tying Motivational Constru...supporting
confidence: 76%
“…4,5 Additionally, types of achievement goal setting, emotional intelligence, and most recently, grit, have been suggested as possible contributing factors to academic performance in pharmacy students. [35][36][37][38][39] A determination of how personality affects academic performance is useful in the context of these varied nonperformance-based factors.…”
Section: Discussionmentioning
confidence: 99%